Effects of ulcerative colitis and Crohn’s disease on neurodegenerative diseases: A Mendelian randomization study - Li, Hong; Wen, Zheng (Frontiers in Genetics, 2022)
Background: Both ulcerative colitis (UC) and Crohn’s disease (CD) are associated with neurodegenerative diseases (NDs) in observational studies, but the causality remains controversial. We aimed to use Mendelian randomization (MR) analysis to explore causal associations between UC and CD and NDs. Methods: We used single nucleotide polymorphisms (SNPs) associated (p < 5 × 10−8) with UC and CD as instrumental variables (IVs) to perform the MR analysis on the risks of three NDs, namely, Alzheimer’s Disease (AD), Parkinson’s Disease (PD), and Amyotrophic Lateral Sclerosis (ALS). The inverse variance weighted (IVW) was the primary method and supplement with the weighted median and MR-Egger regression. Moreover, the MR-Egger intercept test, Cochran’s Q test, and “leave one out” sensitivity analysis were implemented to assess the horizontal pleiotropy, heterogeneities, and stability of these SNPs on NDs. To verify the stability of the results, we re-run the MR analysis by using another set of IVs of UC and CD. A reverse causality analysis was conducted to test whether NDs were causally associated with UC or CD. The significance threshold was set at p < 0.05/6 = 0.008. Results: In the primary MR analysis, the IVW method yielded no evidence to support a causal association between UC and PD (OR: 1.01, 95% CI: 0.96–1.06, p = 0.65), AD (OR: 1.00, 95% CI: 0.99–1.00, p = 0.57), or ALS (OR: 0.98, 95% CI: 0.96–1.01, p = 0.24), and neither did the MR-Egger and weighted median methods. Our MR analysis also suggested no definitively causal effect of the genetically predicted CD on PD (OR: 1.01, 95% CI: 0.97–1.05, p = 0.54), AD (OR: 1.00, 95% CI: 0.99–1.00, p = 0.26), or ALS (OR: 0.99, 95% CI: 0.96–1.02, p = 0.41), as well as MR-Egger and weighted median methods. Consistent results were found in validation analyses. We did not find a significant causal effect of NDs on UC or CD in the reverse MR analysis. Conclusion: No evidence indicated an association between the risks of NDs and genetically predicted UC or CD. The MR results did not support a causal association between UC or CD and three NDs.